Propuesta para mejorar el clima laboral en la empresa florícola Natuflor - Merino Pullas, Karla Antonella (2023)
Work climate is known as the environment that develops among employees within a company or office. The work environment in the company that concerns us presents conflicting, favorable and unfavorable perceptions. The work environment encompasses several dimensions, characteristics or attributes, qualities or property that need to be measured frequently and every year or two. The quality of the work environment directly influences the satisfaction of workers and thus significantly improves productivity. Following this logic, while a good work environment is oriented towards the general objectives of the company, a bad climate destroys the work environment causing situations of conflict or discomfort of employees and this generates low performance, hence the importance of applying surveys for employees that help us measure the level of employee satisfaction. The quality of the work environment is closely related to the social management of managers, with the behavior they have towards workers and the way in which they relate, the interaction they have with the company, as well as the tools used and the characteristics of the employees. The Human Resources department is indicated to evaluate the work environment that exists within the company and thus be able to make decisions to improve it if necessary. A good working environment has a direct impact on employee performance and satisfaction. If it is not the right one, they will not be able to develop their full potential, even if they have the necessary skills to fill the position. Determining and analyzing the state of employee job satisfaction helps companies detect factors that influence the achievement of expected results. Therefore, this research will answer the following questions: How is the work environment of the company Natuflor at this time? What would be an adequate proposal to improve the work environment in relation to the information collected with the research instrument?